PRODUCTION AND INCOME ANALYSIS OF MANGROVE CRAB (Scylla serrata) FARMING IN TANJUNG REJO VILLAGE PERCUT SEI TUAN DISTRICT DELI SERDANG DISTRICT - Yudha Andriansyah Putra; Khairunnisa Rangkuti; Iqbal Ramadhan Daulay (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
Analysis of Production and Revenue of Mangrove Crab Pond (Seylla serrata) Tanjung Rejo Village, Percut Sei Tuan District, Deli Serdang Regency”. The purpose of this study was to analyze the effect of the production factors of pond area, seeds, feed and labor on the production of mud crabs. The selection of research locations was carried out purposively. data collection by distributing questionnaires and interviews. The data sources used are primary data sources and secondary data sources, the sampling method in this study is to use the saturated/census sample method, namely by taking the entire population as a sample. The results showed that the variables of land area and seeds had a significant effect on the production of mud crabs, while the variables of feed and energy did not significantly affect the production of mud crabs. The business income from mangrove crab enlargement in the research area is Rp. 12,503,903.5. with a production period of 3 months. Where the revenue from the mangrove crab enlargement business is Rp. 20,004,736.9 and a total cost of Rp. 11,145,570,16.